Precisely Molded Nanoparticle Displaying DENV-E Proteins Induces Robust Serotype-Specific Neutralizing Antibody Responses. - Stefan W Metz; Shaomin Tian; Gabriel Hoekstra; Xianwen Yi; Michelle Stone; Katie Horvath; Michael J Miley; Joseph DeSimone; Chris J Luft; Aravinda M de Silva (Public Library of Science (PLoS), 2016)
Dengue virus (DENV) is the causative agent of dengue fever and dengue hemorrhagic fever. The virus is endemic in over 120 countries, causing over 350 million infections per year. Dengue vaccine development is challenging because of the need to induce simultaneous protection against four antigenically distinct DENV serotypes and evidence that, under some conditions, vaccination can enhance disease due to specific immunity to the virus. While several live-attenuated tetravalent dengue virus vaccines display partial efficacy, it has been challenging to induce balanced protective immunity to all 4 serotypes. Instead of using whole-virus formulations, we are exploring the potentials for a particulate subunit vaccine, based on DENV E-protein displayed on nanoparticles that have been precisely molded using Particle Replication in Non-wetting Template (PRINT) technology. Here we describe immunization studies with a DENV2-nanoparticle vaccine candidate. The ectodomain of DENV2-E protein was expressed as a secreted recombinant protein (sRecE), purified and adsorbed to poly (lactic-co-glycolic acid) (PLGA) nanoparticles of different sizes and shape. We show that PRINT nanoparticle adsorbed sRecE without any adjuvant induces higher IgG titers and a more potent DENV2-specific neutralizing antibody response compared to the soluble sRecE protein alone. Antigen trafficking indicate that PRINT nanoparticle display of sRecE prolongs the bio-availability of the antigen in the draining lymph nodes by creating an antigen depot. Our results demonstrate that PRINT nanoparticles are a promising platform for delivering subunit vaccines against flaviviruses such as dengue and Zika.